2021
DOI: 10.26434/chemrxiv.14747850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling Extreme Photoreduction Potentials of Donor-Acceptor Cyanoarenes to Access Aryl Radicals from Aryl Chlorides

Abstract: Since the seminal work of Zhang in 2016, donor-acceptor cyanoarene-based fluorophores, such as 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN), have been widely applied in photoredox catalysis, and used as excellent metal-free alternatives to noble metal Ir- and Ru-based photocatalysts. However, all the reported photoredox reactions involving this chromophore family are based on harnessing the energy from a single visible light photon, with a limited range of redox potentials from -1.92 V to +1.79 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…To explore whether the aryl radicals formed could be used for C-C and C-X bond formation, we examined trapping reagents to furnish products 6, 7, and 8 in moderate yields, comparable to those reported using other aryl radical trapping conditions. 15,24,38 Consistent with the propensity of aryl radicals to undergo HAT with weak C-H bonds present on amine reductants and DMPU, we observed that employing DMSO as solvent and sodium formate as the terminal reductant for aryl radical trapping generally improved the selectivity for the desired products over hydrodehalogenation. 12 We anticipate that further improvements could be made with additional optimization: the use of DMSO instead of DMPU was required for selective aryl radical functionalization but led to lower conversion, especially for electron-rich aryl electrophiles.…”
Section: Kinetic Dependence On Light Intensity Kinetic Studies Of The...supporting
confidence: 65%
See 2 more Smart Citations
“…To explore whether the aryl radicals formed could be used for C-C and C-X bond formation, we examined trapping reagents to furnish products 6, 7, and 8 in moderate yields, comparable to those reported using other aryl radical trapping conditions. 15,24,38 Consistent with the propensity of aryl radicals to undergo HAT with weak C-H bonds present on amine reductants and DMPU, we observed that employing DMSO as solvent and sodium formate as the terminal reductant for aryl radical trapping generally improved the selectivity for the desired products over hydrodehalogenation. 12 We anticipate that further improvements could be made with additional optimization: the use of DMSO instead of DMPU was required for selective aryl radical functionalization but led to lower conversion, especially for electron-rich aryl electrophiles.…”
Section: Kinetic Dependence On Light Intensity Kinetic Studies Of The...supporting
confidence: 65%
“…19,21,22 Electrochemistry-primed photoredox catalysis requires a more complex apparatus, leading to challenges in vessel design and scalability. Moreover, the optimal organocatalysts for some strategies require multi-step syntheses and purification, 13,23,24 and can be expensive to use in significant quantities. Therefore, while these strategies have enabled redox-initiated transformations of substrates far beyond the potentials accessible by traditional photocatalysis, these early reports underscore the need for improved photocatalysts with additional stability and access to new mechanisms of reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear relationship with respect to light intensity (Figure 9D) indicated a single-photon process across the measured light intensities. 41 A coordination equilibrium between D and the Zn(II) ions was discovered (Supporting Information, pp S53 and S54); therefore, Sn(0) data is presented for simplicity, although both reactions follow the same trends. Complete data sets for Sn(0) and Zn(0) deposition utilizing Ir1−Ir22 are presented in the Supporting Information (Figures S7−S12).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10 The concept of a two-photon excitation process, commonly purported as a consecutive photoelectron transfer (conPET) pathway, has been reported with numerous notable photocatalysts such as PDI, DCA, anthraquinone, Rhodamine 6G, benzo[ghi]perylene (BPI), 4-DPAIPN, 3-CzEPAIPN, Mes-Acr, and Deazaflavin. [11][12][13][14][15][16][17][18][19] As a common benchmark reaction, photoredox C(sp 2 )-X bond activation in aryl bromides and chlorides, Birch reduction, and sulfonamide cleavage has showcased the extreme photoreducing ability of radical photocatalysts.…”
Section: Introductionmentioning
confidence: 99%